Entwicklung und Evaluierung einer Kommunikationsgestützten Lokalisierung - Hochstein, Maximilian (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2023)
The content of this work is the development of a localization system, which enables several driverless transport vehicles to navigate locally in a highly flexible and free way. The ceiling mounted sensor system detects and analyzes objects within the field of view. The detected properties of all objects are made available via an interface and enable vehicles to identify themselves and navigate freely without a sensor mounted on the vehicle.